First record of Anastrepha pseudoparallela Loew (Diptera: Tephritidae) infesting passion flowers in Peru - Salazar-Mendoza, Paolo (2020)
Several species of the genus Anastrepha Schiner are associated to different hosts and have a great economic importance in fruit crops of the Neotropical region. Ripe and unripe fruits of six passion flowers species were sampled in Oxapampa during 2016 and 2018. Larvae of Anastrepha pseudoparallela Loew (Diptera: Tephritidae) were detected infesting fruits of Passiflora ambigua Hemsl and Passiflora quadrangularis L. For the first time, this fruit fly species is recorded attacking fruits of passion flowers in Peru.